Pengaruh Manajemen Administrasi Keuangan terhadap Keberlanjutan Usaha UMKM Sektor Kuliner di Kota Tangerang - Hartati, Leni; Khoir, Abdul (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
The sustainability of Micro, Small, and Medium Enterprises (MSMEs) continues to face challenges, particularly in financial management practices. This study aims to analyze the effect of financial administrative management on the sustainability of MSMEs in the culinary sector in Tangerang City. This research employs an associative quantitative approach with a sample of 120 MSME actors selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using SEM-PLS with SmartPLS software. The results indicate that all indicators are valid and reliable. The R-square value of 0.47 shows that financial administrative management explains 47% of the variance in business sustainability. The path coefficient of 0.686 with p < 0.05 indicates a positive and significant effect. Effective financial administration through planning, recording, controlling, and reporting has been proven to strengthen MSME sustainability. These findings highlight the importance of enhancing financial administrative capacity as a strategy for business sustainability. The study also recommends the implementation of training and mentoring programs in financial administration for MSME actors to improve the quality of sustainable business management. nical aspects accelerates the adoption of renewable energy and supports environmental, social, and economic sustainability goals.